Bioreactor Engineering Research and Industrial Applications II - Bao, Jie.; Ye, Qin.; Zhong, Jian-Jiang.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book review series presents current trends in modern biotechnology. The aim is to cover all aspects of this interdisciplinary technology where knowledge, methods and expertise are required from chemistry, biochemistry, microbiology, genetics, chemical engineering and computer science. Volumes are organized topically and provide a comprehensive discussion of developments in the respective field over the past 3-5 years. The series also discusses new discoveries and applications. Special volumes are dedicated to selected topics which focus on new biotechnological products and new processes for their synthesis and purification. In general, special volumes are edited by well-known guest editors. The series editor and publisher will however always be pleased to receive suggestions and supplementary information. Manuscripts are accepted in English.
Scale up/scale down of bioreactors -- Process optimization and scale-up using omics analysis -- Perturbation experiments: Experimental approaches for metabolic pathway analysis -- Cell Processing Engineering for Mammalian Cells -- Dry biorefinery process development and bioreactor design for lignocellulose utilization -- Photobioreactor for algal culture -- Novel Hydrogen Detection Apparatus along with Bioreactor Systems -- Self-inducing reactor.
Keywords: Biotechnology; Industrial microbiology; Biotechnology; Chemical Bioengineering; Industrial Microbiology